Assessing Students' Perceptions of AI Grammar and Writing Assistance Tools: Implications for Academic Writing Instruction - Jaya, Sinarman; Susyla, Dian (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Abstract This qualitative study investigates how EFL students view academic writing AI tools (QuillBot, Grammarly, and ChatGPT). This qualitative study examines how English as a Foreign Language (EFL) learners see artificial intelligence (AI) tools for academic writing, including Grammarly, ChatGPT, and QuillBot. Ten seventh-semester students from Muhammadiyah University of Bengkulu's English Study Program were interviewed in order to collect data. The results show that students often utilize these AI tools, with QuillBot being used for paraphrasing, Grammarly mostly for grammar checking, and ChatGPT for idea generation. Eight out of ten students believe that using AI tools to improve their language and sentence structure is beneficial. However, difficulties arise while attempting more difficult tasks, such coherence and logical arguments; some students reported difficulties in maintaining a logical flow in their writing. Students report that while AI tools are helpful for grammar and sentence structure, they are not effective in fostering creativity and critical thinking. They also raised ethical concerns, such as plagiarism and depedence on AI tools. Most of students support the integration of these tools into EFL writing instruction as a complement to traditional methods. It is suggested that educators establish clear guidelines for using AI tools to support students' writing without limiting originality and critical thinking. Keywords: Academic writing, AI grammar assistant, AI writing assisstant, Students’ perceptions